2017
DOI: 10.1021/jacs.7b03005
|View full text |Cite
|
Sign up to set email alerts
|

Cyclobutene vs 1,3-Diene Formation in the Gold-Catalyzed Reaction of Alkynes with Alkenes: The Complete Mechanistic Picture

Abstract: The intermolecular gold(I)-catalyzed reaction between arylalkynes and alkenes leads to cyclobutenes by a [2 + 2] cycloaddition, which takes place stepwise, first by formation of cyclopropyl gold(I) carbenes, followed by a ring expansion. However, 1,3-butadienes are also formed in the case of ortho-substituted arylalkynes by a metathesis-type process. The corresponding reaction of alkenes with aryl-1,3-butadiynes, ethynylogous to arylalkynes, leads exclusively to cyclobutenes. A comprehensive mechanism for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 99 publications
3
55
0
Order By: Relevance
“…We also investigated the possibility of the cyclopropyl gold carbene isomerization that leads to the inversion of the fully substituted carbon center . Although transition states TS iso ( I E7M ‐ I Z7M ) and TS iso ( I E6M ‐ I Z6M ) connecting I E7M / I Z7M and I E6M / I Z6M , respectively, were indeed located, the calculated activation barriers (Δ G ≠ =17.5 and 14.1 kcal mol −1 ; respectively) were found to be incomparable with the O‐ or N‐nucleophilic attack (Δ G ≠ =2.4–5.8 kcal mol −1 , Schemes and ), suggesting this process is irrelevant for this particular reaction system.…”
Section: Resultsmentioning
confidence: 99%
“…We also investigated the possibility of the cyclopropyl gold carbene isomerization that leads to the inversion of the fully substituted carbon center . Although transition states TS iso ( I E7M ‐ I Z7M ) and TS iso ( I E6M ‐ I Z6M ) connecting I E7M / I Z7M and I E6M / I Z6M , respectively, were indeed located, the calculated activation barriers (Δ G ≠ =17.5 and 14.1 kcal mol −1 ; respectively) were found to be incomparable with the O‐ or N‐nucleophilic attack (Δ G ≠ =2.4–5.8 kcal mol −1 , Schemes and ), suggesting this process is irrelevant for this particular reaction system.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that the [2+2] cycloaddition reaction can be applied to aryl‐ and alkyl‐substituted 1,3‐diynes, in which only the terminal alkyne is activated by gold(I) to give rise to 1‐alkynyl cyclobutenes . However, other types of products could be formed as a result of the intramolecular reaction of the cyclopropyl gold(I) carbenes with other functional groups.…”
Section: Introductionmentioning
confidence: 81%
“…Our group developed a gold(I)‐catalyzed intermolecular [2+2] cycloaddition reaction of aryl‐ and cyclopropyl‐substituted terminal alkynes with alkenes to give rise to cyclobutenes regioselectively (Scheme a) . The reaction proceeds satisfactorily in the presence of bulky phosphine gold(I) catalysts, such as A and B .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations